CdII/ZnII discrimination using 2, 5-diphenyl[1, 3, 4]oxadiazole based fluorescent chemosensors. (3rd April 2018) - Formica, Mauro; Ambrosi, Gianluca; Fusi, Vieri; Giorgi, Luca; Arca, Massimiliano; Garau, Alessandra; Pintus, Anna; Lippolis, Vito
Abstract : Two ditopic PPD based ligands are able to discriminate Cd II over Zn II in aqueous solution based on the difference in their ionic radii, acting as OFF–ON fluorescent probes. Abstract : The coordination properties and photochemical response of two fluorescent ligands 2, 5-bis2-[bis(2-pyridylmethyl)aminomethyl]phenyl[1, 3, 4]oxadiazole (L1 ) and 2, 5-bis2-[(1, 4, 7-triazacyclononane-1-yl)methyl]phenyl[1, 3, 4]oxadiazole (L2 ) towards Zn II and Cd II are reported. The ligands contain the 2, 5-diphenyl[1, 3, 4]oxadiazole (PPD) fluorescent probe linked to two coordinating units, namely dipicolylamine (DPA) forL1 and 1, 4, 7-triazacyclononane (TACN) forL2, through a methylene spacer. Both ligands form mononuclear and dinuclear complexes with these metal ions in aqueous or hydro-alcoholic media. With regard toL1, only the mononuclear Cd II complex is highly fluorescent at 368 nm, while the mononuclear Zn II and dinuclear Cd II and Zn II complexes are not emissive. LigandL2 forms an excimer emitting at 474 nm only in the presence of one equivalent of Cd II, and potentiometric, spectrophotometric, spectrofluorimetric, and NMR studies and DFT calculations were performed to explain this peculiarity. The discrimination between Cd II and Zn II is mainly due to the different coordination environments of the metal ions in the mononuclear complexes; namely Cd II is coordinated by both the side arms of each ligand, while Zn II is bound only to one coordinating unit.